Artificial Tendon Driving System Using Skin Effect - (:unkn) unknown (INT ASSOC ENGINEERS-IAENG, 2013)
In this study, skin effect a phenomenon often encountered in high-voltage transport systems was investigated on an artificial tendon. Shape memory alloy (SMA) spring was used as an artificial tendon. The SMA is activated by an electric current, which produces heat and initiates a phase transformation. To create a skin effect, direct current was modified as an alternating input signal with different frequencies using an inverter driving circuit. Skin effect based current signals and direct current signals were applied to the artificial tendon respectively. Comparisons of the effect of two signal feeding techniques were accomplished by constant load-cyclic tests. Another focus of the current study was the solution for SMA's late response problem caused by cooling time.
Keywords: Artificial Tendons; shape memory alloy; skin effect